2019
DOI: 10.7575/aiac.ijels.v.7n.4p.23
|View full text |Cite
|
Sign up to set email alerts
|

The Relations Among University Students’ Academic Self-efficacy, Academic Motivation, and Self-control and Self-management Levels

Abstract: Self-control and self-management, academic motivation and academic self-efficacy are among several variables that affect academic achievement. Although they are widely studied in literature, there is lack of study that deals with them together in one study. This study investigates the relations between self-control and self-management, academic motivation and academic self-efficacy levels of university students. A group of 588 students at a state university in Turkey participated in the study. The data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…This finding is in compliance with many studies in literature (e.g. Schunk, 1991;Bandura, 1993Bandura, , 1997Zimmerman & Kitsantas, 1999;Schunk & Pajares, 2002;Hsieh et al, 2007;Alivernini & Lucidi, 2011;McGeown et al, 2014;Hwang et al, 2015;Eroğlu et al, 2017;Şeker, 2017;Arık, 2019).…”
Section: Figure 2 Results Of the Studysupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in compliance with many studies in literature (e.g. Schunk, 1991;Bandura, 1993Bandura, , 1997Zimmerman & Kitsantas, 1999;Schunk & Pajares, 2002;Hsieh et al, 2007;Alivernini & Lucidi, 2011;McGeown et al, 2014;Hwang et al, 2015;Eroğlu et al, 2017;Şeker, 2017;Arık, 2019).…”
Section: Figure 2 Results Of the Studysupporting
confidence: 93%
“…Self-efficacy affects the quality of life and influences quality and quantity how individuals motivate themselves (Bandura, 2012, p. 13). A positive self-efficacy with a high motivation leads to cope with challenging tasks and raises awareness to show great effort to succeed (Schunk, 1991;Bandura, 1993Bandura, , 1997Schunk & Pajares, 2002;Hsieh, Sullivan & Guerra, 2007;Alivernini & Lucidi, 2011;McGeown et al, 2014;Hwang, Choi, Lee, Culver, & Hutchison, 2015;Arık, 2019). Bandura (1997) contends that self-efficacy plays a larger role in motivation.…”
Section: Academic Self-efficacymentioning
confidence: 99%
“…Drawing from self‐control theory, it is expected that self‐control may mediate the relationship between grit and autonomous learning (Rosenbaum, 1989). Self‐control theory explains that the degree of self‐control can dictate students' academic self‐discipline and learning motivation (Arik, 2019). Students with high self‐control should exhibit high levels of grit, and this in turn, may lead to higher levels of autonomous learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies also found that the approach to self-management has implications for improving independent task performance in all students. (Bahri, Mirnasab, Noorazar, Fathi & Asadi, 2016: Arik, 2019…”
Section: Background Of the Problemmentioning
confidence: 99%